INFLUENCE OF BRISK WALKING EXERCISE ON BLOOD PRESSURE AMONG ESSENTIAL HYPERTENSION PATIENTS - Ika Dwi Rachmawati; Angga Sugiarto; Tulus Puji Hastuti (Midwifery and Nursing Research, 2019)
Latar belakang: Terapi komplementer sekarang menjadi hal biasa dan disukai oleh pasien. Salah satu yang sedang berkembang adalahmterapi komplementer latihan jalan cepat , yang berkorelasi dengan tekanan darah.Tujuan penelitian: untuk membuktikan efek olahraga jalan cepat pada tekanan darah pada pasien dengan hipertensi esensialMethod:This type of research is a quasi exsperiment approach to non equivalent control group design pretest and posttest, where the intervention group of hypertension patients taking anti-hypertensive medication and given treatment in the form of brisk walking exercise 30 minutes for 8 sessions in 2 weeks, while the control group of patients hypertension who just take drugs. Sampling was done by purposive sampling method were 116 patients with essential hypertension were treated in Public health centers Secang 1. Blood pressure measurements performed at the beginning and end of the study. Statistical test using Wilcoxon test and Mann-Whitney.Results: results of the study showed a mean decrease in blood pressure, with significance at p = 0.001 systolic pressure and diastolic pressure of p = 0.001.Kesimpulan: Olahraga jalan cepat dapat dilakukan sebagai terapi komplementer pada pasien dengan hipertensi esensial. Jalan cepat akan berolahraga melawan pembuluh darah sehingga hasil akhirnya dapat menurunkan tekanan darah.